International Journal of Climatology - International Journal of Climatology (Wiley, 2026)
The International Journal of Climatology promotes the study of the climate system from subseasonal to interdecadal timescales through the publication of research papers, major reviews of progress and featured reports across the broad field of climatology. The journal's main role is to stimulate and report the latest research in climatology and its multidisciplinary and transdisciplinary implications.
FI 0.78
Q2
Keywords: Earth; Space & Environmental Sciences; Atmospheric Sciences; Ciencias atmosféricas; Acuerdos transformativos; Transformative agreements; Sistema climático; Climática; Cambio climático